Functional electrical stimulation for facial pacing: Effects of waveforms on movement intensity and ratings of discomfort. (July 2020) - Ilves, Mirja; Rantanen, Ville; Venesvirta, Hanna; Lylykangas, Jani; Vehkaoja, Antti; Mäkelä, Eeva; Verho, Jarmo; Lekkala, Jukka; Rautiainen, Markus; Surakka, Veikko
Highlights: Frontalis of 12 participants was transcutaneously stimulated using four waveforms. All the waveforms produced movements equally successfully. Discomfort ratings did not differ either, but some individual preferences did exist. There was a linear relation between the stimulation amplitudes and evoked movement. Abstract: Facial pacing systems aim to reanimate paralyzed facial muscles with electrical stimulation. To aid the development of such systems, the frontalis muscle responsible for eyebrow raising was transcutaneously stimulated in 12 healthy participants using four waveforms: square wave, square wavelet, sine wave, and sinusoidal wavelet. The aim was to investigate the effects of the waveform on muscle activation magnitude, perceived discomfort, and the relationship between the stimulus signal amplitude and the magnitude of evoked movement. The magnitude of movement was measured offline using video recordings and compared to the magnitude of maximum voluntary movement (MVM) of eyebrows. Results showed that stimulations evoked forehead movement at a magnitude comparable to the MVM in 67% of the participants and close to comparable (80% of the MVM) in 92%. All the waveforms were equally successful in evoking movements. Perceived discomfort did not differ between the waveforms in relation to the movement magnitude, but some individual preferences did exist. Further, regression analysis showed a statistically significant linear relation between stimulation amplitudes and the evoked movement in 98% of the cases. As the waveforms performed equally well in evoking muscle activity, the waveform in pacing systems could be selected by emphasizing technical aspects such as the possibility to suppress stimulation artifacts from simultaneous electromyography measurement.